KADAR KOLAGEN KULIT DAN TULANG PADA TIKUS BETINA USIA ENAM DAN 12 BULAN YANG DISUPLEMENTASI DENGAN SOMATOTROPIN - Ni Wayan Sudatri (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2010)
The objective of this study is to investigate the effects of somatotropin supplementation on skin and bone collagen concentration of six-month and one-year old female mice. Forty eight female rats were assigned into a randomized block design with 4 factors. The first factor was age with 2 levels (6 months and 12 months). The second factor was somatotropin dosage with 2 levels (0 and 9 mg/kg body weight). The third factor was duration of injection with 2 levels (3 weeks and 6 weeks), and the fourth factor was sampling period with 2 levels (0 and 14 days after somatotropin termination). The results showed that somatotropin supplementation had significant effects on bone (P